In Silico characterization of the Phytopathogenic efector, avr3a, from Phytophthora cinnamomi - Branco, Iuliia (2020)
Phytophthora cinnamomi is an Oomycete considered one of the most widespread and destructive pathogens on the planet. Its geographic presence is cosmopolitan and the range of hosts is regarded as one of the largest. This pathogen causes enormous economic damages to important cultures worldwide; this has helped to attract the attention of the scientific community. It is the causal agent of chestnut “ink” disease (Castanea sativa Miller). The chestnut tree has different applications, besides chestnut and wood, it plays an important role in soil ecology and biodiversity. Therefore it is important to know the molecular mechanisms (genes and proteins) that are the basis of the Castanea sativa infestation process by Phytophthora cinnamomi and the nature of the pathogen-host interaction in order to establish strategies to combat and control this parasite. With bioinformatics tools, we were able to identify and characterize the Avr3a gene in genomic sequences of P. cinnamomi deposited in the Databases. This gene encodes a recognized 209 aminoacids, protein in the host cytoplasm where it triggers cell death.